New records, synonymy and description of the male of Culicoides horticola Lutz, 1913 (Diptera: Ceratopogonidae) - Felippe Bauer, María Luiza (2009)
The male of Culicoides horticola Lutz, 1913 is described and illustrated from specimens collected in the Department of Madre de Dios, Peru, and in the State of Rio de Janeiro, Brazil. Culicoides bachmanni Spinelli, 2005 is considered as a junior synonym of C. horticola. Previous citations and descriptions of C. horticola are discussed, and the species is firstly recorded from Peru and biting humans.